“Reading Enjoyment” is Ready for School: Foregrounding Affect and Sociality in Children’s Reading for Pleasure - Boyask, R; Harrington, C; Milne, J; Smith, B (Springer Science and Business Media LLC, 2022)
While debate on declines in children’s literacy is ongoing in Aotearoa New Zealand, very little attention in research and policy is paid to reading enjoyment and its capacity to support the reading development of children. Developed alongside a series of studies on children’s reading for pleasure this article makes a theoretically informed argument to place reading enjoyment at the centre of literacy education in schools. Our argument is underpinned by a psycho-social conceptualisation of enjoyment that emphasises the fundamental sociality of emotion. Foregrounding affect and sociality in children and young people’s reading speaks to the potential of teachers being with children and their whānau together reading for pleasure. When children are at school they can participate in the sociality of reading for pleasure, sharing its enjoyment with other class members and teachers without coming into conflict with the priorities of life outside of school. If schools embed reading enjoyment in their programmes, they might then have greater capacity to follow the literacy and communication strategy and work towards sharing the collective enjoyment of reading with families, whānau, and communities.
Keywords: Reading enjoyment; Reading for pleasure; Children’s reading; Affect; Literacy education